Prevalence of upper limb disorders and associated factors with psychosocial and awkward postureamong public university workers in Malaysia - Mahmood Khudhir, Karwan; Ariffin, Ahmad Azuhairi; Kadir @ Shahar, Hayati (International Organization of Scientific Research, 2015)
Musculoskeletal disorders of the upper limb are a most important cause of ill-health, incapacity and health care expenditure. The purpose of this study is to determine the prevalence of Upper Limb Disorders associated with awkward posture and psychosocial factors among Universiti Putra Malaysia (UPM) workers. Simple random sampling was used to draw 271 participants from six faculties of the university. The use of a structured question was employed for data collection. Results of the study showed thatprevalence of ULDs among UPM workers was 67.2% in different body regions. Results showed that there is a significant association between ULDs and age, awkward posture, control at work, psychological demand, social support, and job satisfaction) (p<0.05). Multivariate logistic analysis showedthat the workers who had medium and very high RULA risk level were 12.242 times more likely to complain about ULDs (OR=12.242, 95%CI: 3.617-41.435), compared to other workers who have low RULA risk level.In conclusion, it can be said from the result of the study that there is high prevalence of upper limb disorders among UPM workers which is significantly associated with age, awkward posture and all psychosocial factors. In order to minimize the prevalence rate of upper limb disorders, it is recommended that workers be educated on prevention strategies and an ergonomic program which emphasizes psycho-social risk factors and how to improve working conditions.